1999
DOI: 10.1002/(sici)1521-3765(19990104)5:1<113::aid-chem113>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

The Designed Self-Assembly of Multicomponent and Multicompartmental Cylindrical Nanoarchitectures

Abstract: The polytopic linear 4 and circular 5 ligands undergo self-assembly with copper(i) and silver(i) ions to generate the large inorganic entities 2 and 3 containing, two and three internal cavities, respectively. The process amounts to the spontaneous assembly of a total of 15 and 19 particles to yield multicompartmental architectures. The crystal structures of two such complexes have been determined. They confirm the nature of the entities formed and show that in addition several substrate species (anions and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(85 citation statements)
references
References 10 publications
0
83
0
2
Order By: Relevance
“…One of the first examples of a heteroleptic three-dimensional metal-organic architecture was reported by Lehn and co-workers in 1993, 41,42 who reported that the slow addition of a Cu I salt (6 equivalents) to a mixture of 3 equivalents of rigid quaterpyridine ligand 24 and 2 equivalents of the hexaazatriphenylene 27 ligand in acetonitrile resulted in the formation of complex 28 (Fig. 9).…”
Section: Heteroleptic Structuresmentioning
confidence: 97%
“…One of the first examples of a heteroleptic three-dimensional metal-organic architecture was reported by Lehn and co-workers in 1993, 41,42 who reported that the slow addition of a Cu I salt (6 equivalents) to a mixture of 3 equivalents of rigid quaterpyridine ligand 24 and 2 equivalents of the hexaazatriphenylene 27 ligand in acetonitrile resulted in the formation of complex 28 (Fig. 9).…”
Section: Heteroleptic Structuresmentioning
confidence: 97%
“…This process represents the remarkable self-organization of a closed inorganic architecture from multiple components by means of the spontaneous and correct assembly, in one stroke, of eleven particles belonging to two types of ligands and one type of metal ion. Analogous cylindrical architectures of an even larger size, presenting three and four layered features, have been obtained using similar procedures (Baxter et al, 1999). Of particular interest are architectures of the rack, ladder and grid types (Figure 7).…”
Section: Self-organization By Design: Programmed Chemical Systemsmentioning
confidence: 99%
“…Thus, the bicompartmental 64 and tricompartmental 65 complex cations were generated in a single operation by selfassembly from the corresponding stoichiometric mixtures of ligand components of two different types and metal ions (Figure 20). In addition, X-ray structural determinations and 1 H NMR solution studies revealed that the multicellular architectures encapsulated anions in their cavities 134 .…”
Section: The Designed Self-assembly Of Multicomponent and Multicomparmentioning
confidence: 99%